Refolding of autodisplayed anti-NEF scFv through oxidation with glutathione for immunosensors - Bong, Ji-Hong; Song, Hyun-Woo; Kim, Tae-Hun; Kang, Min-Jung; Jose, Joachim; Pyun, Jae-Chul (ELSEVIER ADVANCED TECHNOLOGY, 2018)
In this study, a single-domain antibody against negative regulatory factor (anti-NEF scFv) was autodisplayed on the outer membrane of Escherichia colt and used to detect NEF in an immunoassay based on fluorescence-activated cell sorting, enzyme-linked immunosorbent assay, and surface plasmon resonance biosensors. Next, the autodisplayed single-domain antibody was oxidized to form disulfide bonds by using glutathione, and the change in NEF-binding activity of anti-NEF scFv was analyzed by fluorescence-activated cell sorting-based immunoassay, chromogenic immunoassay, and surface plasmon resonance biosensor. For each type,of immunoassays the anti-NEF scFv on the isolated outer membrane showed more NEF binding activity after the disulfide bond formation by glutathione. To determine the role of cysteines in anti-NEF scFv, three mutants were prepared, and the NEF binding activity of mutants was compared with that of wild-type anti-NEF scFv in a competitive immunoassay based on FACS. In these mutant studies, the refolding process of autodisplayed anti-NEF scFv by following oxidation via GSH/GSSG revealed that disulfide bonds formed and increased NEF binding activity.
Keywords: ESCHERICHIA-COLI-CELLS; OUTER-MEMBRANE LAYER; LIGAND-BINDING ASSAYS; Z-DOMAINS; E. COLI; SPR BIOSENSOR; VARIABLE DOMAINS; IMMUNOASSAY; PROTEIN; STABILITY